2013
DOI: 10.1016/j.foreco.2013.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Optimal nitrogen application rates for three intensively-managed hardwood tree species in the southeastern USA

Abstract: a b s t r a c tForest production can be limited by nutrient and water availability, and tree species are expected to respond differently to fertilization and irrigation. Despite these common expectations, multi-species comparisons are rare, especially ones implementing a range of fertilization rates crossed with irrigation. This study compares the response of three forest hardwood species to numerous nitrogen (N) fertilization levels and water availability using a novel non-replicated technique. A range of N l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…We hypothesized that increased resource availability would positively influence above and belowground growth, productivity, and biomass accumulation of each species tested (e.g. Cobb et al, 2008;Brinks et al, 2011;Coyle et al, 2013). We also hypothesized that previously reported differences in growth, productivity, and biomass accumulation among species (Coyle and Coleman, 2005;Coyle et al, 2008) would be maintained throughout the rotation.…”
Section: Introductionmentioning
confidence: 96%
“…We hypothesized that increased resource availability would positively influence above and belowground growth, productivity, and biomass accumulation of each species tested (e.g. Cobb et al, 2008;Brinks et al, 2011;Coyle et al, 2013). We also hypothesized that previously reported differences in growth, productivity, and biomass accumulation among species (Coyle and Coleman, 2005;Coyle et al, 2008) would be maintained throughout the rotation.…”
Section: Introductionmentioning
confidence: 96%
“…Two pure P. deltoides clones ('ST66' of Mississippi origin and 'S7C15' of East Texas origin) were included in this study that measured growth and productivity responses to varying levels of irrigation and fertilization. In a non-replicated experiment designed to find optimal nitrogen fertilization rates [28], the optimal nitrogen fertilization rates were 131 and 71 kg N ha −1 year −1 for irrigated and non-irrigated 'ST66', respectively. Maximum aboveground biomass differed little, however, between irrigated and non-irrigated trees (i.e., range from 3.6 to 4.3 dry Mg ha −1 year −1 ).…”
Section: Cottonwoodmentioning
confidence: 99%
“…In the southeastern USA, the growth and productivity of sycamore and sweetgum grown with a range of water and nutrient availability were evaluated in two separate experiments on the Upper Coastal Plain of South Carolina. After 8 years, Coyle et al [28] found that the optimal fertilization rates were 147 and 141 kg N ha −1 year −1 for irrigated and nonirrigated sycamore, respectively. The productivity of sycamore receiving irrigation was 6.5 dry Mg aboveground woody biomass per hectare per year, a 20 % increase over the biomass production rate without irrigation.…”
Section: American Sycamore and Sweetgummentioning
confidence: 99%
“…Research using a similar experimental design in temperate forests of North America tends to find that fertilisation has stronger effects on tree growth, whereas the effects of irrigation are weaker and often only manifest themselves when fertilisation is applied (Coyle & Coleman, ; Coyle et al, ). This highlights how dryland forests are likely to respond differently to management regimes than those of temperate regions, which are more likely to be nutrient‐limited than water‐limited (Coyle et al, ). Previously, Eucalyptus species grown in drylands showed positive responses to increased water availability (Tomé et al, ; Reed & Tomé, ), whereas those grown in humid conditions frequently do not (Misra et al, ; Adams et al, ).…”
Section: Discussionmentioning
confidence: 99%